MODAL SOSIAL PADA TRADISI PACU JALUR DALAM MASYARAKAT DESA SUNGAI SORIK KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI - Prihatin, Audisia Ulfa; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was carried out on the society of sungaisorik village, kuantanhilirsebrangSub-district which especially on the society regulator of the village. The purpose of this research was to find out the social capital and the meaning of the symbols which was used in the pacujalur Tradition by Sungai Sorik villagers. The theory used is the social capital theory proposed by Fukuyama which consists of Trust, social networks, values and norms. This type of research uses a descriptive qualitative approach. Subjects in this study were 7 people, which 3 people in charge of the pacujalur, 2 shamans and 2 athletes of pathways. The sampling technique used in this research was purposive sampling technique, where sampling was taken by selecting objects (informants) based on specific criteria set by the researcher. Data sources used are data sources in the form of observation (observation) and interviews (Interview). Analysis of the data used in this study with data collection techniques from various sources by including the theory used in accordance to the social phenomenas. The results of this researchwere that social capital is very important in managing pacujalur in Sungai Sorik Village, Kuantan Hilir Sub-district, across Kuantan Singingi Regency. A believe is an important element in the society organization with their respective positions in the management of pacujalur to progress the this event in Sungai Sorik Village. The social network that was formed cannot be separated from the collaboration so as to form a network, such as between fellow shamans, the administrators, athletes, sponsors and village communities. Values and norms served as guidelines for all parties, including the administrators, shamans,athletes and regulator communities, the values and norms that apply are traditions that have existed since a long time ago and must be maintained without losing them from the pacujalur tradition. The meaning of the symbols used in pacujalur tradition is still used till today because that was a uniqueness of that event.Keywords: Social Capital, Pacu jalur Tradition, Meanings of Symbols